2017
DOI: 10.3390/ijerph14111417
|View full text |Cite
|
Sign up to set email alerts
|

Is School Type Associated with Objectively Measured Physical Activity in 15-Year-Olds?

Abstract: The main aims of this study were: (1) to determine the objectively assessed physical activity (PA) patterns in urban 15-year-old male and female adolescents according to school type and (2) to assess the differences in PA between school days and weekend days. In this cross-sectional study, participants were 187 secondary-school male and female adolescents (61.4% females) attending grammar and vocational schools. Patterns of PA were objectively evaluated using a multi-sensor body monitor for 5 consecutive days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…This study is a part of the CRO-PALS, an observational, longitudinal study designed to investigate the health-related habits and risk behaviour among the adolescents in the city of Zagreb (Croatia) during their 4-year-long high-school education. The sampling procedure and study design have been described thoroughly elsewhere [ 25 , 26 ]. In brief, to select a representative group of urban adolescents, a stratified two-phase random sampling method was applied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is a part of the CRO-PALS, an observational, longitudinal study designed to investigate the health-related habits and risk behaviour among the adolescents in the city of Zagreb (Croatia) during their 4-year-long high-school education. The sampling procedure and study design have been described thoroughly elsewhere [ 25 , 26 ]. In brief, to select a representative group of urban adolescents, a stratified two-phase random sampling method was applied.…”
Section: Methodsmentioning
confidence: 99%
“…In line with the PA guidelines for Canadians (2002) and the review of Janssen and LeBlanc (2010) [ 38 , 39 ], activities requiring EE between 4 and 7 METs were classified as MPA whereas activities requiring above 7 METs were categorised as VPA. To determine the average of MPA and VPA daily we multiplied the average school day value by 5 and the average weekend day value by 2 and then divided the score by 7, according to the formula: MPA, VPA = ((MEANschooldays ∗ 5) + (MEANweekend days ∗ 2))/7, as described previously [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study was performed during the second wave of assessments, and all measurements were taken in 2015, during March, April, and May. Information about the procedures of the CRO-PALS longitudinal study have been documented in previous research [ 26 ]. In brief, using stratified two-stage random sampling procedures (school level and class level), 54 classes in 14 secondary schools were selected to participate in the CRO-PALS study (schools were stratified by type: grammar schools/vocational schools/private schools).…”
Section: Methodsmentioning
confidence: 99%
“…The current study is part of the Croatian Physical Activity in Adolescence Longitudinal Study (CRO-PALS), an observational, longitudinal study that investigated behaviors of adolescents in the city of Zagreb (Croatia) throughout the four years of high school education. The sample size estimation and selection for the CRO-PALS study has been reported in detail elsewhere [22]. Briefly, a stratified two-stage random sampling procedure was employed to select an adequately large representative sample of urban adolescents.…”
Section: Study Participantsmentioning
confidence: 99%